2016
DOI: 10.1080/17476348.2017.1267568
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous oxygen: a novel method of oxygen delivery in hypoxemic respiratory failure?

Abstract: Hypoxemic respiratory failure is a common problem in critical care. Current management strategies, including mechanical ventilation and extracorporeal membranous oxygenation, can be efficacious but these therapies put patients at risk for toxicities associated with invasive forms of support. Areas covered: In this manuscript, we discuss intravenous oxygen (IVO), a novel method to improve oxygen delivery that involves intravenous administration of a physiologic solution containing dissolved oxygen at hyperbaric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Applying this method to the supplemental bicarbonate dialysis fluid, a significant increase in the pO 2 and simultaneous decrease in the partial pressure of carbon dioxide (pCO 2 ) were observed [8]. Gehlbach et al suggested that an intravenous (IV) supersaturated solution might also improve hypoxia in critically ill patients with respiratory failure [9].…”
Section: Introductionmentioning
confidence: 99%
“…Applying this method to the supplemental bicarbonate dialysis fluid, a significant increase in the pO 2 and simultaneous decrease in the partial pressure of carbon dioxide (pCO 2 ) were observed [8]. Gehlbach et al suggested that an intravenous (IV) supersaturated solution might also improve hypoxia in critically ill patients with respiratory failure [9].…”
Section: Introductionmentioning
confidence: 99%
“…51 , 52 IVO 2 is an alternative to invasive methods of alveolar gas exchange (such as ECMO), providing direct oxygen delivery through IV administration of a physiologic oxygen solution at concentrations exceeding normal atmospheric pressure to hypoxemic patients. 53 Historically, the first application of IVO 2 using simple gaseous oxygen was introduced by Nysten in the early 19th century. 54 In 1902, the first oxygen administration to a living human via the IV route was performed by Mariani.…”
Section: Brief History Of Ivo 2 Therapymentioning
confidence: 99%
“…However, recent studies have proven that IVO 2 delivered by NBs is a noninvasive technique that could be safe enough to be included in the arsenal for hypoxemic respiratory failure. 53 Another concern is related to premature oxygen release during the vascular injection of ONBs, which could be overcome by the development of various chemical or biological formulations to decline the surface tension and to improve the stability of ONBs in the human body. Free ONBs that are not coated and stabilized by any component in the shell structure dissolve quickly in the circulation, while the use of surfactants, lipids, proteins, and their combinations can avoid disproportionation, coalescence, and undesired oxygen release.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
See 2 more Smart Citations